The immature stages and biology of two Xenapates species in West Africa (Hymenoptera, Tenthredinidae) - Liston, A.D.; Goergen, Georg E.; Koch, F. (Pensoft Publishers, 2015)
The immature stages and host plants of Xenapates Kirby, 1882 were hitherto unknown. We describe the larvae, prepupae and pupae of X. braunsi (Konow, 1896) and X. gaullei (Konow, 1896), and record observations on aspects of their biology. The relationship of Xenapates to other taxa currently placed in the Allantinae and Blennocampinae of the Tenthredinidae remains unclear. Most larval characters of Xenapates resemble those described for West Palaearctic Allantini (Allantinae) and some Blennocampinae, but unique amongst exophytic larvae of Tenthredinoidea is the complete absence of cuticular appendages on the dorsum of the trunk in the two Xenapates species studied. The setose outer surface of the abdominal prolegs of Xenapates, and the presence of a mesal ridge only on the left mandible, are character states that have not so far been recorded in other genera currently placed in the Allantinae or Blennocampinae. Larval host plants of X. braunsi are Digitaria horizontalis, Pennisetum purpureum, Setaria barbata and Zea mays (all Poaceae). X. gaullei larvae feed on two Commelina species (Commelinaceae). Larvae of both species are easy bleeders.